Green finance as a mechanism for achieving food security under climate change: The case of Algeria - Farida, Sellat; BELOUADAH, Abdelaziz (The International tax journal, 2025)
The agricultural sector represents a fundamental pillar of food security, especially in developing countries such as Algeria. However, it faces increasing climatic challenges, most notably the decline of water resources and land degradation. In this context, green finance has emerged as an innovative mechanism to support the transition towards sustainable and resilient agricultural systems. Green finance refers to the allocation of financial resources to projects that take environmental considerations into account, such as smart agriculture, modern irrigation systems, renewable energy, and the development of drought-resistant seeds. This research paper aims to identify the role of green finance in achieving food security in Algeria. The study concludes that, despite the efforts made by Algeria to achieve sustainable food security, it still suffers from the absence of an environmental orientation in banks’ environmental products.